2015
DOI: 10.1186/s13045-015-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the long non-coding RNA PVT1 is correlated with leukemic cell proliferation in acute promyelocytic leukemia

Abstract: BackgroundAcute promyelocytic leukemia (APL) is associated with chromosomal translocation t(15;17), which results in the proliferation of morphologically abnormal promyelocytes. Gain of supernumerary copies of the 8q24 chromosomal region, which harbors MYC and PVT1, has been shown to be the most common secondary alteration in human APL. Increased MYC can accelerate the development of myeloid leukemia in APL. However, the role that the expression of the long non-coding RNA (lncRNA) PVT1 plays in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 47 publications
(46 reference statements)
7
70
0
2
Order By: Relevance
“…Around the same time, studies showed that the PVT1 gene locus also underwent a variant translocation in human Burkitt’s lymphomas [10, 11]. The PVT1 gene is located on chromosome 8, a recognized cancer risk locus shared with the well-known MYC oncogene_ENREF_12, suggesting that PVT1 is a potential oncogene [12]. In vitro experiments have demonstrated that PVT1 could promote proliferation, migration and invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Around the same time, studies showed that the PVT1 gene locus also underwent a variant translocation in human Burkitt’s lymphomas [10, 11]. The PVT1 gene is located on chromosome 8, a recognized cancer risk locus shared with the well-known MYC oncogene_ENREF_12, suggesting that PVT1 is a potential oncogene [12]. In vitro experiments have demonstrated that PVT1 could promote proliferation, migration and invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…As lncRNAs have emerged as important participants in the pathogenesis and disease progression of AML, [66][67][68][69][70][71][72][73][74] it is likely that profiling of their expression would have significant impact on MDS prognostication. Recently, it has been shown that lncRNA expression signatures were closely associated with specific mutations and a small subset of lncRNAs could predict clinical outcome in cytogenetically normal elderly AML patients, 75 but the clinical significance of lncRNA profiling in MDSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be highly expressed in a series of human tumors, including breast and ovarian cancers, acute myeloid leukemia, and Hodgkin lymphoma. [19][20][21] Nonetheless, the expression and biological effect of PVT1 on glioma vascular endothelial cells remain unknown.…”
Section: Pvt1 Affects Growth Of Glioma Microvascular Endothelial Cellmentioning
confidence: 99%